Antidiabetic and TNF-α Lowering Effect of Tagetes erecta Extract in Alloxan-Induced Diabetic Rats - Prajawanti, Kadeq Novita; Negara, Yohanes Ardian Kapri; Arianing, Intan Febiola; Junitasari, Fitri (Borneo Journal of Pharmacy, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by impaired insulin production or action, often leading to pancreatic β-cell dysfunction and apoptosis. Pro-inflammatory cytokines, notably Tumor Necrosis Factor-alpha (TNF-α), play a critical role in the pathogenesis of type 2 diabetes (T2D). While Tagetes erecta (marigold) has demonstrated potential in lowering blood glucose in hyperglycemic conditions, its anti-inflammatory effects in diabetic models remain underexplored. This study aimed to evaluate the antidiabetic and TNF-α lowering effects of T. erecta extract in alloxan-induced diabetic rats. Twenty-five male Wistar rats were divided into a normal control group (n=5) and a diabetic group (n=20) induced by alloxan (blood glucose ≥126 mg/dL). Diabetic rats were then randomized into four treatment subgroups (n=5 each): untreated diabetic control, and diabetic groups treated with T. erecta extract at doses of 25 mg/kg BW, 50 mg/kg BW, or 75 mg/kg BW (administered intraperitoneally). Statistical analysis revealed that T. erecta extract significantly reduced blood glucose levels in alloxan-induced diabetic rats (p <0.05). Furthermore, the highest dose of T. erecta extract (75 mg/kg BW) effectively attenuated elevated TNF-α levels, demonstrating a significant anti-inflammatory effect. In conclusion, this study provides compelling evidence that T. erecta extract exhibits both antidiabetic and anti-inflammatory properties by significantly lowering blood glucose and TNF-α levels in alloxan-induced diabetic rats, particularly at the 75 mg/kg BW dose.